Urban Law, Territorial Planning and Challenges Imposed by COVIC-19 Pandemic - Ortiz Sánchez, Iván (2020)
COVID-19 Pandemic has created different challenges for Peruvian cities. How Urban Law and urban regulation should respond to those challenges? The article tries to respond to this question by revisiting the concept of Urban Law and the principles that are behind it. Moreover, the article will explore the impacts that the social distancing policies have had in territorial planning, public transport and public spaces and how this new context requires a reframe in the policies that regulate those sectors. The final section is dedicated to highlighting the importance of housing in the social distancing context and how the housing regulation should evolve to create a real safe-place from the risks imposed by the COVID-19 that allows the continuity of life in this new reality.